Tingkat Keterampilan Bertanya Guru SLTP dalam Komunikasi Pembelajaran - Maryono Maryono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Skills of Questioning among Junior-high-school Teachers in Classroom Interaction. The aims of the study were to investigate the level of questioning skills among junior-high-school teachers in the teaching-learning process and to explore factors contributing to the development of questioning skills. The subjects involved were 15 teachers (10 % of the population) of Indonesian, English, and Social Studies. The data were collected through a questionnaire and observation, which were then analyzed using regression, analyses of variance, correlation, and t-test. The results show that the majority of the teachers reflect questioning skills which are of fair category and only 20% of very good category. The study also reveals that training contributes to the development of questioning skills (67.14 %).